PERANCANGAN APLIKASI SISTEM PENJUALAN AIR MINUM DALAM KEMASAN PADA PT. GAJAH ASRI RAYA - Lena Magdalena; Triana Ramadani (TeIKa, 2018)
Along with the development of the times, technological advances, especially computers are always growing rapidly. Among them in terms of accounting activities that are currently using the computer as a means of processing and storage of data. PT. Gajah Asri Raya is manufacturing company that still apply the manual system in process of recording sales reports. Record keeping and accounting reports over its sales still made manually, so it often raises some constraints such as the creation of a sales report takes relatively long time as a result can not meet the information needs of the nonprofit soon. To minimize the constraints that occur from manual system that have been run by the company, in the journal this time manual process were developed to become computerized. This system is implemented by using the Visual Basic programming language that are expected to assist in managing the accounting logging data on sale to make it more accurate, structured, and can save you time. The result of the implementation of computer-based sales information system indicates that the accounting process more quickly and precisely than by using a manual method: with notes notebook manuals and the Microsoft Excel affect the speed of decision making in the management of the company.